2017
DOI: 10.5530/ijper.51.3.64
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Evaluation of an OSCE in Undergraduate Doctor of Pharmacy Program

Abstract: Introduction and purpose: In schools not performing OSCE method, faculty members' lack of time, human resources and managing the complexity of such exam are the most common obstacles. In this study, we utilized different methods to evaluate the the validity and reliability of a simple diversified OSCE as part of final exam for ambulatory care clerkship along with the theoretical exam. Methods: We analyzed the correlation and difference between students' achievements in the written exam and their achievements i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
(14 reference statements)
1
5
1
Order By: Relevance
“…There were some differences in the extent of students' agreement with this statement in favor of penultimate students and nal year students from a private university. In contrast, previous research conducted to explore students' opinions regarding the objectivity and validity of OSCE has highlighted that students had different views on the acceptance of the OSCE as the main evaluation assessment of their clinical skills (Alkhathlan et al, 2018;Almuqdadi et al, 2017). Overall, the participants in our study were found to have a good acceptance level of the OSCE to evaluate their clinical skills.…”
Section: Discussioncontrasting
confidence: 79%
“…There were some differences in the extent of students' agreement with this statement in favor of penultimate students and nal year students from a private university. In contrast, previous research conducted to explore students' opinions regarding the objectivity and validity of OSCE has highlighted that students had different views on the acceptance of the OSCE as the main evaluation assessment of their clinical skills (Alkhathlan et al, 2018;Almuqdadi et al, 2017). Overall, the participants in our study were found to have a good acceptance level of the OSCE to evaluate their clinical skills.…”
Section: Discussioncontrasting
confidence: 79%
“…There were some differences in the extent of students' agreement to this statement in favour of penultimate students and final year students from a private university. In contrast, previous research conducted to explore students' opinions regarding the objectivity and validity of OSCE has highlighted that students were having different views on the acceptance of the OSCE as the main evaluation assessment of their clinical skills (Almuqdadi et al, 2017;Alkhathlan et al, 2018). Overall, the participants in our study had a good acceptance level of the OSCE to evaluate their clinical skills.…”
Section: Discussionmentioning
confidence: 94%
“…The OSCE is a practical examination that provides a standardized assessment of clinical competence [1]. Since the OSCE formula was first described by Harden in 1975 [2], it has been the subject of numerous studies and has been widely adopted by educational institutions, particularly in the health sciences (Medicine, Pharmacy, Odontology) [3][4][5][6]. The OSCE tests are today considered as the gold standard for the evaluation of clinical competence [7,8].…”
Section: Introductionmentioning
confidence: 99%